2020
DOI: 10.3390/polym12091935
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation of Polystyrene (PS) Nanocomposites Loaded with Sol Gel-Synthesized ZnO Nanorods

Abstract: Thermal degradation of polystyrene/ZnO (PS/ZnO) nanocomposites was investigated in this study. PS/ZnO polymer nanocomposites were prepared by using ZnO nanorods as nanofillers that were prepared via the sol-gel route. The as-prepared ZnO nanoparticles showed nanocrystallites in rod-like shapes with a non-uniform hexagonal cross-section and diameter varying from 40 to 75 nm. PS/ZnO nanocomposites with ZnO nanoparticles content ranging from 0–3 wt% are prepared via the common casting method. Even dispersion for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…S3b† shows that the endothermic peak temperature of the original PS was 416 °C, while the melting peak temperature ( T m ) increased to 424 °C after 60 days of weathering, slightly deviating from a typical endothermic peak range of 440–450 °C. 39 It was found that T m progressively increased gradually with prolonged weathering, resulting in enhanced thermal stability. Given that PS is a highly crystalline polymer, the variations in T m could be ascribed to changes in crystallinity.…”
Section: Resultsmentioning
confidence: 99%
“…S3b† shows that the endothermic peak temperature of the original PS was 416 °C, while the melting peak temperature ( T m ) increased to 424 °C after 60 days of weathering, slightly deviating from a typical endothermic peak range of 440–450 °C. 39 It was found that T m progressively increased gradually with prolonged weathering, resulting in enhanced thermal stability. Given that PS is a highly crystalline polymer, the variations in T m could be ascribed to changes in crystallinity.…”
Section: Resultsmentioning
confidence: 99%
“…Pristine CNC showed a drastic weight loss attributed to the CNC carbonization around 300–350 °C, after which it remained constant at 700 °C. On the other hand, CNC@PVPA went a weight loss of about 30% from 200 to 300 °C attributed to intramolecular dehydration in PVPA. , Then, there was a gradual decrease in weight between 300 and 450 °C for CNC@PVPA and between 300 and 500 °C for CNC@PVPA- b -PS. This difference in weight loss temperature was considered to be due to the inhibition of the CNC carbonization and PVPA main chains by the polystyrene coating . After a gradual decrease, a drastic weight loss attributed to carbonization of the main alkyl chain of PVPA and PS was observed between 450 and 500 and 500 and 550 °C for CNC@PVPA and CNC@PVPA- b -PS, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This difference in weight loss temperature was considered to be due to the inhibition of the CNC carbonization and PVPA main chains by the polystyrene coating. 39 After a gradual decrease, a drastic weight loss attributed to carbonization of the main alkyl chain of PVPA and PS was observed between 450 and 500 and 500 and 550 °C for CNC@PVPA and CNC@PVPA-b-PS, respectively. Finally, a mild decrease was observed until 700 °C.…”
Section: ■ Experimental Sectionmentioning
confidence: 95%
“…Uniformly dispersed clay within the matrix polymer can enhance T i D by acting as a masstransfer barrier for the volatile products generated during decomposition. [48][49][50] That is, polymer degradation may be delayed as the clay content increases in the hybrid lm. This effect can be explained by the fact that the mobility of the polymer chains decreases as the nanosized clay particles become more evenly dispersed because inorganic clays are nondegradable materials with a very large surface area.…”
Section: Thermal Propertymentioning
confidence: 99%